2017
DOI: 10.3329/bjms.v16i2.23421
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of apical microleakage of different root canal sealers by apical dye penetration

Abstract: Abstract:Objective: This study was designed to compare the level of apical microleakage of root canal sealers; Acroseal, AH Plus, Endoflas FS and Endomethasone N, with laterally condensed gutta percha by level of apical dye penetration. Materials and Methods: Freshly extracted sixty permanent maxillary anterior teeth were divided randomly into four groups. Shaping and cleaning of teeth was done followed by obturation with gutta percha and four different root canal sealers. Samples were immersed in 2% methylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The results of observations and dye penetration measurements in this study showed that in all groups of obturation material occurred apical microleakage. The results are in agreement with Ayer et al, 9 which states that all root canal obturation materials allow marginal infiltration and are not impenetrable.…”
Section: Discussionsupporting
confidence: 92%
“…The results of observations and dye penetration measurements in this study showed that in all groups of obturation material occurred apical microleakage. The results are in agreement with Ayer et al, 9 which states that all root canal obturation materials allow marginal infiltration and are not impenetrable.…”
Section: Discussionsupporting
confidence: 92%
“…However, this did not apply to the ZOE-based sealers due to a longer setting time of around 24-36 hours, and nonacceptable flow rates. 14,15,22 The characteristics of the ZOE-based sealer caused some samples in this treatment group to experience an incomplete setting so the sealer material dissolved when the samples were immersed in the methylene blue dye. This assumption served as the basis for obtaining insignificant differences between the ZOE-based sealer and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have been conducted to evaluate the apical sealing ability of bioceramicbased sealers. 1,15,16 However, there are no studies conducted to compare this material with the most commonly used standard sealer material, namely ZOE. This study aimed to compare the apical sealing ability of bioceramic-based and ZOEbased sealers in root canal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Stereomicroscope was calibrated prior to observation, digital images of specimens had been captured using attached camera(OptikamB5, Italy) on a stereomicroscope (19) ,linear dye penetration leakage from root apex to the most coronal extent of dye penetration was measured in millimeters, and scored by scoring system (20) .Dye apical leakage was scored :Score 0: if there was no leakage, score 1: if leakage was less than or equal 0.5 mm, score 2: if leakage was from 0.51mm to less than 1 mm and score 3: if leakage was more than 1 mm (14) .…”
Section: Stereomicroscopic Observationmentioning
confidence: 99%